2002
DOI: 10.1152/ajpgi.00276.2002
|View full text |Cite
|
Sign up to set email alerts
|

IV. Clinical and physiological aspects of gastrointestinal motility and aging

Abstract: Control of the GI Tract. IV. Clinical and physiological aspects of gastrointestinal motility and aging. Am J Physiol Gastrointest Liver Physiol 283: G1226-G1231, 2002; 10.1152/ajpgi.00276. 2002.-The gastrointestinal motility changes that occur as a function of age are reviewed herein. Careful attention must be given in any review of aging phenomena to exclude, or at least be cognizant of, the many comorbid conditions that can alter physiological functioning in older adults. The dramatic increase in life expec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(60 citation statements)
references
References 23 publications
0
54
0
5
Order By: Relevance
“…Other studies have shown that elderly patients presented with lower amplitude of contractions in the distal esophagus and lower number of complete relaxation of the LES (12,13,20) . Recent studies in the elderly show that both the sensory function, and visceral perception were significantly decreased with advanced age (15,17,18,22) . Despite all these findings, few studies were done to investigate the effect of age on esophageal motility of patients with achalasia.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Other studies have shown that elderly patients presented with lower amplitude of contractions in the distal esophagus and lower number of complete relaxation of the LES (12,13,20) . Recent studies in the elderly show that both the sensory function, and visceral perception were significantly decreased with advanced age (15,17,18,22) . Despite all these findings, few studies were done to investigate the effect of age on esophageal motility of patients with achalasia.…”
Section: Resultsmentioning
confidence: 99%
“…Estimated that the world population aged over 65 will double over the next 40 years (1,7) . Moreover, it is known that with advancing age there is a decrease in function in several body organs, and among the several changes observed, motility of the gastrointestinal tract is also included (4,9,10,11,17,19) . It has been shown manometric findings similar to those observed in patients with achalasia (decrease in distal esophageal amplitude and complete relaxation of LES) in asymptomatic elderly people with no comorbidity (12,13,17,20) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The change in neuronal profile is justified by those authors as an adaptive condition to progressive neuronal loss with age, as greater functional demand is required from these neurons, which could result in a state of cellular hypertrophy. This reflects the plasticity of enteric neurons; thus, the degenerative processes resulting from age can be offset by the plasticity of the ENS, and changes in gastrointestinal motility take place only when the functional reserves of the neurons are spent (Orr and Chen 2002).…”
Section: Effect Of Ascorbic Acid On Myenteric Neurons Of Ratsmentioning
confidence: 99%